A Standalone, Battery‐Free Light Dosimeter for Ultraviolet to Infrared Light. (17th December 2021) - Van der Heggen, David; Zilenaite, Rugile; Ezerskyte, Egle; Fritz, Verena; Korthout, Katleen; Vandenberghe, Dimitri; De Grave, Johan; Garrevoet, Jan; Vincze, Laszlo; Poelman, Dirk; Joos, Jonas J.; Smet, Philippe F.
Abstract: Light sensors are widely used to monitor light intensities, for instance in medical applications, in agriculture or for conservation of art. Most of these sensors are electronic devices that record continuously but applications that only require information of integrated intensities, measured over a long time, could greatly benefit from an integrating dosimeter that does not require a power supply. In this work a wireless and quantitative light dosimeter is presented based on SrAl2 O4 :Eu 2+, Sm 3+, a phosphor that exhibits stable energy storage upon exposure to blue and ultraviolet light. It is shown that a forward electron transfer from europium to samarium can be induced under illumination with blue or ultraviolet light while the reverse electron transfer can be achieved by illuminating the phosphors with green to infrared light. This reverse transfer is accomplished through excitation of the divalent samarium and results in bright, green optically stimulated luminescence. The stable energy storage, in combination with the possibility for optical read‐out, makes SrAl2 O4 :Eu 2+, Sm 3+ ideally suited to be used as an integrating light dosimeter for monochromatic to broadband light, from the ultraviolet to the near infrared. To demonstrate this, a proof of concept dosimeter was developed in which this phosphor was successfully used to measure average daylight intensities. Abstract : Luminescent materials that exhibits stable energy storage after exposure to ultraviolet and blue light can be used to develop a wireless and reusable integrating light sensor. This sensor technology allows to obtain quantitative information on cumulative light intensities and bridges the gap between powered, continuously recording electronic light sensors and nonelectronic indicators which offer only qualitative information.